Carcass composition, muscle morphology, and meat characteristics for the red jungle fowl (Gallus gallus spadicious Linnaeus), village chicken, and commercial broiler - Idris, Lokman Hakim (2011)
The current study was carried out with the main aim to define the morphology of muscle and to evaluate the meat characteristic of Red Jungle Fowl and Malaysian Village chicken which are known to have slow growth rates and an attempt was made to compare with the commercial broiler chicken which is known to have a fast growth rate. To our knowledge there is no data documented on the carcass composition of the Red Jungle Fowl and Village Chicken muscle at different ages. A total of 150 chickens from three different breeds were used in this study, they were Red Jungle Fowl (RJ), Malaysian Village Chicken (VC) and Commercial Broiler (CB) with 50 chickens for each breed. The eggs of RJ and VC were collected from Jenderam Hulu, Sepang, Selangor, hatched in the incubator and reared in the experimental house. The CB were collected from the CP (M) Private Limited hatchery in Kuala Kangsar, Perak as Day 1 chicks and reared in the same experimental house. All the chickens were given starter (201C) commercial feed from Day 1 to Day 21 and finisher (203 P) commercial feed from Day 22 to Day 120 post hatch and water was provided ad libitum. Ten chickens from each breed were serially euthanized at Day 1, 10, 20, 56 and 120 post hatch. The pectoralis major was used to represent breast muscle and bicep femoris representing the thigh muscle. The muscle samples were fixed in 10% formalin for histological examination. Muscle fiber typing was done to evaluate the types of muscle fiber composition by acidic myosin ATPase staining. The proximate analysis was done using oven method for moisture and dry matter, furnace method at 600°C for ash and Kjeldahl method for the crude protein. The collagen contents in muscles were measured by analysing the hydroxyproline using spectrophotometer. The fatty acids were determined by GLC after extraction and methylation and the amino acid concentration was determined by HPLC. The muscle samples were also evaluated for the meat characteristic including colour, pH, cooking loss and shear force. There were no significant different (P>0.05) in the whole carcass, meat, bone and fat weights for the RJ, VC and CB at Day 1. However, as the age increased the RJ showed significantly (P<0.05) lower whole carcass, meat, bone and fat weights followed by VC and while CB. The meat to bone ratio in RJ was 30 % higher than the VC at Day 56 and 120 post hatch, but 50% and 40% lower than CB at Day 20 and 120 respectively. The RJ has lightest meat weight among the three breeds. The RJ had the smallest muscle bundle area, diameters of fibers in the breast and thigh muscles followed by the VC, while the CB was the highest. There were increases in the number of fibers in the breast and thigh muscles at Day 10 to 20 post hatch and at Day 56 to day 120 for RJ and VC. The RJ breast and thigh muscles had significantly (P<0.05) higher Type I and lower Type II muscle fiber followed by VC and CB at all different ages evaluated. Type I fibers in the thigh muscle were nearly 50% higher than the breast muscle and Type II muscle fiber was 10.25%, 5.4% and 5.7% lower in RJ, VC and CB respectively in the thigh muscle compared to the breast muscle. There were changes of Type II to Type I muscle fiber as the age increased. The crude protein of breast in RJ and VC were significantly (P<0.05) higher than the CB at Day 20 and 56 post hatch. The crude protein at younger ages (Day 1) were significantly (P<0.05) higher than at older ages (Day 120). The crude protein were 19.78 %, 20.40% and 20.04% in RJ, VC and CB breast muscle respectively at Day 120 and 20.57 %, 22.09% and 24.06% respectively at Day 1 post hatch. The composition of MUFA was lower, but the composition of PUFA was higher in the RJ and VC compared to the CB breast muscles. Within the breeds the composition of total MUFA were decreased as the age increased and the composition of total PUFA were increased as the age increased. The total MUFA and PUFA showed no significant difference (P>0.05) between the breast and thigh muscles at different ages evaluated. Maternal diets were the main factors in determining the composition of fatty acid and amino acid at Day 1 and Day 10 post hatch. Within the breeds, the composition of amino acids increased as the age increased a reflected by the growth of the muscle in suggesting different catabolism, metabolism and absorption rates among the breeds. The pH of the breast muscle in RJ was the highest (6.18, 5.89 and 5.96 at day 20, 56 and 120 respectively) followed by VC (6.09, 5.85 and 5.70 at day 20, 56 and 120 respectively) and CB (5.89, 5.76 and 5.74 at day 20, 56 and 120 respectively) while for the thigh muscle, there was no significant difference (P>0.05) between the three breeds. Comparing the breast and thigh muscles regardless of the breeds, generally, the pH of thigh muscle was significantly higher (P<0.05) than the breast muscle. The colour of breast and thigh muscles of RJ and VC appeared more reddish (a*) and less lightness (L*) compared to the CB. In general, the colour of breast muscle of RJ, VC and CB appeared lighter and more yellow than the thigh muscle, while the thigh muscle appeared more reddish than the breast muscle. There was negative correlation between pH and L* value (r = - 0.48) and positive correlation to the a* value (r = 0.43) in all breeds and ages evaluated. The b* value also showed positive correlation (r = 0.4) to the pH in all breeds and ages evaluated. The total collagen contents in the muscle increased as the age increased for all the three breeds evaluated. Total collagen contents in the breast and thigh muscles were significantly higher in the RJ followed by the VC and CB, and the collagen contents of the thigh muscles were higher than the breast muscle. Thus, the shear force values were higher in RJ followed by VC and CB and the shear force value in the thigh muscle was higher than the breast muscle in all breeds evaluated, and consequently producing less tender meat. There was a positive correlation of collagen content and shear force value in both breast and thigh muscles (r = 0.61). The cooking loss of breast and thigh muscles in RJ and VC were higher compared to the CB and the thigh muscle were higher cooking loss than the breast muscle. The pH value showed a negative correlation (r = - 0.2) with the cooking loss but the results revealed that the amount of collagen was more important than the pH itself in determining the cooking loss. Cooking loss also showed a positive correlation (r = 0.48) with the shear force value. The RJ had a lower meat yield, less tender meat with a low water holding capacity. However, the meat contained less fat, higher crude protein, higher meat to bone ratio and were reddish in colour compared to CB. The VC parameters were always midway between the two breeds. The present study contributes to the knowledge of the field of study in the morphology and meat characteristic as well as to improve the breeds of local birds for a better quality meat.